Food and nutrition security support groups A safety net strategy for sustaining gains from a livelihood program in Uganda - Moureen Mbeiza; Caroline Nambafu; David Banige; Samuel Ikendi; Dorothy Masinde; Lee Burras; Gideon Nadiope; Francis Owusu (Lyson Center for Civic Agriculture and Food Systems, 2026)
Introduction In 2015, world leaders set the target to achieve zero hunger by 2030 through the launch and operationalization of the Sustainable Development Goals (United Nations, 2015). However, progress reports show that the world is still off track, with projections indicating persistent hunger and malnutrition (Food and Agriculture Organization [FAO] et al., 2024; 2025). These reports are synonymous with the global hunger index, which has consistently marked Uganda as serious in hunger severity (Scherer et al., 2025). Moreover, the 2024 national census also showed that 46% of Ugandans were experiencing food insecurity (Uganda Bureau of Statistics, 2024), and trend studies and models indicated increasing levels of food and nutrition insecurity in the country (Akumu et al., 2023; Maniragaba et al., 2023; Ogenrwoth et al., 2022). The government of Uganda has directly invested in interventions to improve food and nutrition security (FAO, 2024, p. 180; Office of the President, 2025) and through public-private partnerships (Office of the Prime Minister, 2020) to ensure consistent food production to nourish the population and sustain the gains. These partnerships are consistent with the sustainable livelihood programs of our study between Uganda and the U.S. (Butler & Acker, 2015; Ikendi & Retallick, 2025; Ikendi, Mwenyi & Retallick, 2025; Thurow, 2024).